Cytotoxicity and immunomodulatory effects of sol-gel combustion based titanium dioxide (TiO2) particles of large surface area on RAW 264.7 macrophages. (September 2017) - Dinesh, Palani; Suresh Yadav, C.; Kannadasan, Sathanandhan; Rasool, Mahaboobkhan
Abstract: The current study was designed to investigate the cytotoxicity and immunomodulatory effects of sol-gel combustion based TiO2 particles (glycine andl -alanine as reducing agents) of large surface area on RAW 264.7 macrophages. RAW 264.7 macrophages exposed to varying concentrations of TiO2 particles (0.001 to 1000 μg/ml) were assessed after 24 h and showed a reduced cell viability at 100 and 1000 μg/ml and increased LDH release at 10 μg/ml. Furthermore, TiO2 particles (0.1, 1 and 10 μg/ml) were utilized to assess the immune responses and intracellular ROS levels on RAW 264.7 macrophages. TiO2 particles at 10 μg/ml showed increased mRNA expression of inflammatory cytokines (TNFα, IL-1β and IL-6), inflammatory mediators (iNOS and COX-2) and transcription factor (NFκB) similar to that of LPS stimulated macrophages. However, the mRNA expression levels were found near normal levels at lower concentrations (0.1 and 1 μg/ml). In addition, TiO2 particles at 10 μg/ml also increased the production of inflammatory cytokines (TNFα, IL-1β and IL-6) and intracellular ROS levels in RAW 264.7 macrophages similar to that of LPS stimulated macrophages. Conclusively, TiO2 particles prepared through this method at a concentration ≤ 0.1 μg/ml can be used for various biological applications with minimal immunomodulatory effects. Graphical abstract: Highlights: Sol-gel combustion based TiO2 particles (glycine andl -alanine as reducing agents). In vitro cytotoxicity analysis of TiO2 particles of large surface area. Immune responses of low concentrations of TiO2 particles. ROS levels of cells exposed to TiO2 particles.